Rethinking the Russian Revolution as historical divide
1 online resource
Keywords: "The Russian Revolution of 1917 has often been presented as a complete break with the past, with everything which had gone before swept away, and all aspects of politics, economy, and society reformed and made new. Recently, however, historians have increasingly come to question this view, discovering that Tsarist Russia was much more entangled in the processes of modernisation, and that the new regime contained much more continuity than has previously been acknowledged. This book presents new research findings on a range of different aspects of Russian society, both showing how there was much change before 1917, and much continuity afterwards, and also going beyond this to show that the new Soviet regime established in the 1920s, with its vision of the New Soviet Person, was in fact based on a complicated mixture of new Soviet thinking and ideas developed before 1917 by a variety of non-Bolshevik movements."--Provided by publisher.